Development of a project for modernizing the working equipment of a universal forklift with a load capacity of 2.5 tons to enhance work efficiency - Mohid, Soumia (Харківський національний автомобільно-дорожній університет, 2023)
The design object is the working equipment of a compact loader. The project's objective is to develop special working equipment for a forked loader - a swivel carriage, providing the ability to move the load in a horizontal plane. The purpose of the designed equipment is its utilization in the operation of the loader under constrained conditions. In the project, a swivel carriage has been developed with a rotation angle of up to 90º in the horizontal plane, intended for efficient loading and stacking of loads with minimal maneuvering of the loader in both directions. The swivel frame of the carriage is standardized with the loader's carriage plate. Therefore, the swivel carriage can work with any standardized load handling device.
Keywords: carriage; load; swing; mechanism